Multiple Valence Bands Convergence and Localized Lattice Engineering Lead to Superhigh Thermoelectric Figure of Merit in MnTe - Shahzada Zulkifal; Zhichao Wang; Xuemei Zhang; Suniya Siddique; Yuan Yu; Chong Wang; Yaru Gong; Shuang Li; Di Li; Yongsheng Zhang; Peng Wang; Guodong Tang (Advanced Science, 2023)
Abstract MnTe has been considered a promising candidate for lead‐free mid‐temperature range thermoelectric clean energy conversions. However, the widespread use of this technology is constrained by the relatively low‐cost performance of materials. Developing environmentally friendly thermoelectrics with high performance and earth‐abundant elements is thus an urgent task. MnTe is a candidate, yet a peak ZT of 1.4 achieved so far is less satisfactory. Here, a remarkably high ZT of 1.6 at 873 K in MnTe system is realized by facilitating multiple valence band convergence and localized lattice engineering. It is demonstrated that SbGe incorporation promotes the convergence of multiple electronic valence bands in MnTe. Simultaneously, the carrier concentration can be optimized by SbGeS alloying, which significantly enhances the power factor. Simultaneously, MnS nanorods combined with dislocations and lattice distortions lead to strong phonon scattering, resulting in a markedly low lattice thermal conductivity(κlat) of 0.54 W m K−1, quite close to the amorphous limit. As a consequence, extraordinary thermoelectric performance is achieved by decoupling electron and phonon transport. The vast increase in ZT promotes MnTe as an emerging Pb‐free thermoelectric compound for a wide range of applications in waste heat recovery and power generation.